Enterovirus as trigger of coeliac disease: nested case-control study within prospective birth cohort - Kahrs, Christian R; Chuda, Katerina; Tapia, German; Stene, Lars C; Mårild, Karl; Rasmussen, Trond; Rønningen, Kjersti S; Lundin, Knut E A; Kramna, Lenka; Cinek, Ondrej; Størdal, Ketil (BMJ (Clinical research ed.), 2019)
OBJECTIVE: To determine whether infection with human enterovirus or adenovirus, both common intestinal viruses, predicts development of coeliac disease. DESIGN: Case-control study nested within Norwegian birth cohort recruited between 2001 and 2007 and followed to September 2016. SETTING: Norwegian population. PARTICIPANTS: Children carrying the HLA genotype DR4-DQ8/DR3-DQ2 conferring increased risk of coeliac disease. EXPOSURES: Enterovirus and adenovirus detected using real time polymerase chain reaction in monthly stool samples from age 3 to 36 months. MAIN OUTCOME MEASURE: Coeliac disease diagnosed according to standard criteria. Coeliac disease antibodies were tested in blood samples taken at age 3, 6, 9, and 12 months and then annually. Adjusted odds ratios from mixed effects logistic regression model were used to assess the relation between viral infections before development of coeliac disease antibodies and coeliac disease. RESULTS: Among 220 children, and after a mean of 9.9 (SD 1.6) years, 25 children were diagnosed as having coeliac disease after screening and were matched to two controls each. Enterovirus was found in 370 (17%) of 2135 samples and was significantly more frequent in samples collected before development of coeliac disease antibodies in cases than in controls (adjusted odds ratio 1.49, 95% confidence interval 1.07 to 2.06; P=0.02). The association was restricted to infections after introduction of gluten. High quantity samples (>100 000 copies/μL) (adjusted odds ratio 2.11, 1.24 to 3.60; P=0.01) and long lasting infections (>2 months) (2.16, 1.16 to 4.04; P=0.02) gave higher risk estimates. Both the commonly detected enterovirus species Enterovirus A and Enterovirus B were significantly associated with coeliac disease. The association was not found for infections during or after development of coeliac disease antibodies. Adenovirus was not associated with coeliac disease. CONCLUSIONS: In this longitudinal study, a higher frequency of enterovirus, but not adenovirus, during early childhood was associated with later coeliac disease. The finding adds new information on the role of viral infections in the aetiology of coeliac disease.
Keywords: Feces; Celiac Disease; Enterovirus Infections; Male; Child, Preschool; longitudinální studie; kvantitativní polymerázová řetězová reakce; Risk Factors; Autoantibodies; Genotype; Enterovirus; Infant; Child; Norway; dítě; Case-Control Studies; Prospective Studies; mužské pohlaví; celiakie; Real-Time Polymerase Chain Reaction; předškolní dítě; lidé; ženské pohlaví; studie případů a kontrol; Humans; autoprotilátky; kojenec; rizikové faktory; Longitudinal Studies; genotyp; Norsko; Female; feces; enterovirové infekce; prospektivní studie